Ceratonova shasta infection in Sacramento River Chinook salmon - John Scott Foott (California Fish and Wildlife Journal, 2025)
Field surveys and sentinel studies were conducted with juvenile Chinook salmon (Oncorhynchus tshawytscha) in the Sacramento River between 2012 and 2022. Both Ceratonova shasta and Parvicapsula minibicornis were common myxozoan parasites of both juvenile and adult Chinook salmon. C. shasta infection was found to be associated with morbidity and clinical disease among sampled juvenile salmon in multiple years. This finding demonstrates that disease is another adverse survival factor for juvenile salmon in the Sacramento River. In 2016 and 2018, river water was assayed for C. shasta spore concentration with peak values occurring near Red Bluff Diversion Dam. In some years, C. shasta may reduce juvenile salmon survival. Monitoring water-borne spore stages and salmon infection would inform how flow management influences the parasite lifecycle in the Sacramento River.